Pengaruh Jenis Mulsa terhadap Kapasitas Penambatan Spesifik Nitrogen Cemara Udang (Casuarina equisetifolia Linn.) pada Kondisi Tempat Tumbuh yang Berbeda - A. Triyogo; , Sumardi; D. A. Winastuti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
Nitrogen fixation's processes on the plants are determined by numbers of roots nodule formed on rootery system and by their ability to fix the nitrogen. The activity of root nodule in nitrogen fixation's processes gives a great contribution for the plant growth. The aim of this research is to study the effect of mulch types on the forming root nodule and also the capacity of air nitrogen specific fixation of C. equisetifolia Linn. with different site conditions. This research use split-split plot design with factorial treatment. The plants of C. equisetifolia Linn. were planted on three different sites using three kinds of mulch. The (approach) method used to find out the forming of root nodule was to count  the numbers and the dry weight of root nodule, while the measurement of the capacity of root nodule on the nitrogen fixation used the Acethylene Reduction Capacity method (ARA). The result of this research showed that the site of underground growth white sand beach had the best forming root nodule. For the mulch treatment, straw mulch showed the best nitrogen fixation ability, that was 13.8x10-9n g N2/g nodule dry weight/days and for interaction treatment, straw mulch at lime stone with inoculation showed the highest nitrogen fixation that was 26.45x10-9n g N2/g nodule dry weight/days.   Key words: nitrogen specific fixation, Casuarina equisetifolia Linn., growth